Preparation method and application of Co-based oxide material based on g-C3N4 anchoring

By preparing Co-based oxide gas sensing materials based on defect-rich g-C3N4 anchorage, the synergistic effect of defects and heterostructures is used to solve the problem of high working temperature and poor selectivity of ethanol gas sensors in the prior art, and the rapid, sensitive and highly selective detection of trace ethanol is achieved.

CN119701856APending Publication Date: 2025-03-28DALIAN INSTITUTE OF CHEMICAL PHYSICS CHINESE ACADEMY OF SCIENCES

Patent Information

Application Number
CN202311253308.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-09-26
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

The existing semiconductor metal oxide ethanol gas sensors have the disadvantages of high operating temperature and poor selectivity, making it difficult to achieve rapid and sensitive detection of trace ethanol.

Method used

By preparing a Co-based oxide gas sensing material based on defect-rich g-C3N4 anchorage, the defect site of g-C3N4 is used to achieve the attachment of metal ions, and the in-situ growth of MOFs is formed to form a Co3O4 nanostructure, combining the synergistic effect of defects and heterostructures to improve gas sensing performance.

Benefits of technology

It realizes fast, sensitive and highly selective detection of trace ethanol. The sensor has the characteristics of high sensitivity, fast response recovery speed, good selectivity, and low cost and simple operation.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119701856A_ABST
    Figure CN119701856A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method and application of a Co-based oxide material based on g-C3N4 anchoring, and the preparation method comprises the following steps: (1) calcining an N-containing precursor I to obtain g-C3N4; (2) etching g-C3N4 with an alkaline solution, centrifuging I, and drying I to obtain g-C3N4 rich in defects; and (3) reacting a mixture of the g-C3N4 rich in defects, a Co precursor, 2-methylimidazole and a solvent, centrifuging II, drying II and calcining II to obtain the Co-based oxide material based on g-C3N4 anchoring. The prepared g-C3N4 is rich in defects, more sites are provided for ion adsorption, and subsequent high-load metal oxide generation is facilitated. A heterostructure formed between g-C3N4 and Co3O4, a built-in electric field formed at an interface and defects at the interface greatly improve the gas sensing response.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to a preparation method and application of a Co-based oxide material anchored by g-C3N4, belonging to the technical field of nano-functional materials and environmental monitoring. Background Art

[0002] As an important chemical raw material, ethanol is widely used in food processing, medical and industrial production. However, long-term exposure to ethanol gas can not only cause headaches, liver and kidney dysfunction, but also paralyze the central nervous system. In addition, as a flammable gas, its vapor mixed with air can cause explosions, so it is very necessary to detect ethanol in production and life.

[0003] At present, semiconductor metal oxides for detecting ethanol have disadvantages such as high operating temperature and poor selectivity. Therefore, the modification and modification of semiconductor metal oxides are of great significance for improving ethanol gas sensors. Among many methods, the construction of heterogeneous interfaces has attracted widespread attention from researchers due to its advantages such as simple preparation methods and diverse construction methods. In addition, in heterogeneous interfaces, since there is usually a certain degree of lattice mismatch between the two phases constituting the heterostructure, the formed heterogeneous structure has a large number of lattice defects at the interface. These lattice defects can serve as active sites for gas adsorption, thereby greatly improving the gas sensing performance.

[0004] Defects, as intrinsic properties of materials, promote gas adsorption and gas-sensitive sensing reactions. Defects, as the most reactive sites in materials, can enhance the accessibility of materials to target gas molecules, thereby improving gas sensing performance. Combining defects with heterogeneous interfaces and utilizing the synergistic effect between the two can achieve the effect of "1+1>2". Summary of the invention

[0005] The mechanism of semiconductor resistance gas sensor to detect target gas molecules is to change the resistance of the sensor by the reaction between the absorbed target gas molecules and the chemically adsorbed oxygen species on the surface of the sensing material, and detect the concentration of the target gas by the change of resistance under the condition of the target gas. The determination of the gas concentration is achieved by establishing the relationship between the gas concentration and the change of the resistance value.

[0006] Researchers have found that the gas sensing performance of metal oxides is closely related to size, structure and morphology. A high BET specific surface area is conducive to increasing the contact between the gas and the material surface, thereby improving the gas sensing performance. As a material with a pore structure, MOFs can facilitate gas mass transfer due to its porous structure. In addition, the presence of a porous structure is conducive to further improving the material's adsorption capacity for target gas molecules, thereby ultimately improving the gas sensing response.

[0007] In addition, the surface electronic regulation of metal oxide semiconductor materials is conducive to further improving the gas sensing response ability of the materials. Since it is difficult for single-component materials to simultaneously meet the requirements of high sensitivity, high selectivity and stability, heterogeneous composite gas sensing materials that integrate two or more components have received extensive attention and research. The existence of a heterogeneous structure can cause two materials with different band gaps to bend at the heterogeneous interface, which can improve the electronic transmission ability of the material. In addition, the integration of materials of different components can have a synergistic effect of "1+1>2" to achieve a significant improvement in gas sensing performance.

[0008] The purpose of the present invention is to provide a low-cost and simple-to-operate preparation of a Co-based oxide gas sensing material based on defect-rich g-C3N4 anchoring, and to use the metal oxide in a gas sensor to achieve rapid and sensitive detection of trace amounts of ethanol in production and life.

[0009] Based on this purpose, the present invention first prepared a new type of Co-based oxide gas sensing material based on defect-rich g-C3N4 anchoring, firstly realized the attachment of metal ions by using the defect sites on g-C3N4, and then realized the in-situ growth of MOFs with it as the center. In addition, in the subsequent gas sensing process, the synergistic effect of defects and heterogeneous structures achieved a significant improvement in gas sensing performance.

[0010] According to one aspect of the present application, a method for preparing a Co-based oxide material based on g-C3N4 anchoring is provided, the preparation method comprising the following steps:

[0011] (1) calcining the N-containing precursor to obtain g-C3N4;

[0012] (2) etching the g-C3N4 with an alkaline solution, centrifuging I, and drying I to obtain defect-rich g-C3N4;

[0013] (3) A mixture of defect-rich g-C3N4, Co precursor, 2-methylimidazole, and solvent is reacted, centrifuged II, dried II, and calcined II to obtain the Co-based oxide material anchored by g-C3N4.

[0014] Optionally, in step (1), the N-containing precursor is selected from at least one of melamine, urea and dicyandiamide.

[0015] Optionally, the mass volume ratio of the g-C3N4 to the alkaline solution is 0.5-1 g: 10-20 mL.

[0016] Optionally, in step (2), the alkaline solution is selected from NaOH and / or KOH.

[0017] Optionally, the concentration of the alkaline solution is 0.1M to 0.5M.

[0018] Optionally, the concentration of the alkaline solution is selected from any value among 0.1M, 0.2M, 0.3M, 0.4M, 0.5M or a range between any two of the above values.

[0019] Optionally, the mass ratio of the Co precursor, defect-rich g-C3N4, and 2-methylimidazole is 0.5g~1g: 0.01g~0.05g: 0.01g~0.05g, wherein the mass of the Co precursor is calculated by its own mass, the mass of the defect-rich g-C3N4 is calculated by its own mass, and the volume of the solvent used is calculated by its own volume.

[0020] Optionally, the Co precursor is selected from at least one of cobalt chloride, cobalt nitrate, cobalt acetate and organic cobalt.

[0021] Optionally, the organic cobalt is selected from at least one of cobalt acetylacetonate and cobalt naphthenate.

[0022] Optionally, the solvent is selected from at least one of methanol, water and ethanol.

[0023] Optionally, the etching time is 12 to 24 hours.

[0024] Optionally, in step (3), the reaction temperature is 20 to 80° C., and the reaction time is 1 to 24 hours.

[0025] Optionally, the number of centrifugation I and centrifugation II is independently selected from 3 to 7 times.

[0026] Optionally, the temperatures of drying I and drying II are independently selected from 50 to 85° C., and the times of drying I and drying II are independently selected from 12 to 16 hours.

[0027] Optionally, the temperatures of calcination I and calcination II are independently selected from 500 to 700° C., and the times of calcination I and calcination II are independently selected from 4 to 6 hours.

[0028] According to another aspect of the present application, a Co-based oxide material based on g-C3N4 anchoring prepared by the above-mentioned preparation method is provided, characterized in that the Co-based oxide in the Co-based oxide material based on g-C3N4 anchoring is Co3O4;

[0029] The loading amount of Co3O4 in the g-C3N4 anchored Co-based oxide material is 5wt% to 20wt%.

[0030] According to another aspect of the present application, there is provided an application of the above-mentioned g-C3N4 anchored Co-based oxide material in an ethanol gas sensor, wherein the detection limit of the ethanol gas sensor is 300 to 350 ppb.

[0031] Optionally, the detection limit of the ethanol gas sensor for ethanol is selected from any value of 300 ppb, 310 ppb, 320 ppb, 330 ppb, 350 ppb or a range between any two of the above values.

[0032] Optionally, the operating temperature of the ethanol gas sensor is 100-150°C.

[0033] As a specific implementation, the present invention is implemented by the following technical solutions:

[0034] 1. A preparation method of a Co-based oxide gas sensing material anchored by defect-rich g-C3N4 and its application in ethanol gas sensing, the preparation method comprising the following preparation steps:

[0035] Step a, preparing a Co-based oxide gas sensing material anchored by defect-rich g-C3N4;

[0036] Step b, constructing an ethanol gas sensor;

[0037] Among them, the specific steps of step a for preparing Co-based oxide gas sensing materials based on defect-rich g-C3N4 anchoring are:

[0038] (1) g-C3N4 was prepared by thermal polymerization of a N-containing precursor. 5 g of the N-containing precursor was placed in a crucible and heated from room temperature to 550°C in a muffle furnace at a heating rate of 5°C / min. The temperature was maintained at 550°C for 4 h. After the muffle furnace was cooled to room temperature, g-C3N4 was obtained.

[0039] (2) Defect-rich g-C3N4 was obtained by liquid phase chemical etching. 0.5 g of g-C3N4 obtained in (1) was dissolved in 1 M NaOH, stirred at room temperature, and the product was collected, centrifuged, washed, and dried to obtain defect-rich g-C3N4.

[0040] (3) The g-C3N4-Co MOFs composite structure was obtained by liquid phase electrostatic adsorption. 0.1 g of cobalt nitrate and 0.5 g of defect-rich g-C3N4 in (2) were dissolved in 40 ml of methanol, marked as solution A. Solution B was prepared by dissolving a certain amount of 2-methylimidazole in 40 ml of methanol. At ambient temperature, under constant magnetic stirring at 1500 rpm, solution B was slowly poured into solution A for a certain period of time. The product was collected by centrifugation, washed and dried to obtain the g-C3N4-Co MOFs composite structure.

[0041] (4) g-C3N4-Co3O4 is obtained by calcining the precursor. The g-C3N4-Co MOFs composite structure obtained in (3) is placed in a crucible and maintained at 500°C for 4 hours with a heating rate of 5°C / min. After cooling to room temperature, g-C3N4-Co3O4 is obtained.

[0042] Step b: The specific construction steps for building the ethanol gas sensor are:

[0043] (1) Using the interdigital electrode as the gas sensing electrode, add the prepared sample to an appropriate amount of solvent and mix to form a uniform slurry. Evenly drop the slurry on the electrode surface to form a film. Dry the interdigital electrode in an oven to evaporate the solvent to obtain a sensing film.

[0044] (2) The electrode obtained in step (1) is then aged in an oven to remove the organic solvent remaining on the electrode, thereby obtaining a gas sensing electrode with stable resistance. The gas sensing electrode is connected to a test instrument to obtain an ethanol gas sensor.

[0045] Optionally, in step (1), the solvent is selected from at least one of ultrapure water, anhydrous ethanol, and acetone.

[0046] 2. The gas sensor based on the two-dimensional metal oxide gas-sensitive material is applied to the detection of ethanol gas molecules, and its characteristics are that the specific detection method is:

[0047] (1) Using interdigital electrodes as gas sensing electrodes, 5-10 μL of slurry was dropped onto the surface of the substrate with Ag-Pd printed interdigital electrodes. The electrodes were dried at 65-100°C to form a sensing film.

[0048] (2) The modified interdigital electrode is heated in an oven to 180-200° C. for 12-24 hours to remove the residual organic solvent, thereby obtaining an ethanol gas sensor to be tested.

[0049] (3) The gas sensor test is carried out using the static gas distribution method, that is, a certain amount of ethanol liquid is evaporated on a hot stage using a micro-injector to obtain a certain concentration of ethanol gas. The vaporized ethanol gas evaporates in the test chamber, and the ethanol gas molecules are detected by recording the resistance change of the sensor before and after the gas is introduced.

[0050] (4) Record the initial resistance of the sensor in air as R a , different concentrations of ethanol were introduced into the test chamber, and the resistance when the gas was introduced was recorded as R g , with R g With R aDraw a working curve based on the relationship between the ratio and the concentration of ethanol gas molecules.

[0051] The present invention uses defect-rich g-C3N4 as a substrate material and defect sites as ion adsorption sites. First, a composite structure of g-C3N4-Co MOFs is obtained, and then a g-C3N4-Co3O4 nanostructure is obtained through subsequent calcination. The material shows a highly sensitive response to trace amounts of ethanol. The constructed sensor has the characteristics of high sensitivity, fast response recovery speed, good selectivity, etc. g-C3N4 has a well-known two-dimensional sheet structure, which provides a large specific surface area for the loading of metal oxides. In addition, the g-C3N4 prepared by the invention is rich in defects, which provides more sites for the adsorption of ions, which is conducive to the subsequent generation of high-load metal oxides. The heterogeneous structure formed between g-C3N4 and Co3O4, the built-in electric field formed at the interface and the defects at the interface greatly improve the gas sensing response. The successful preparation of the material provides a new idea for the synthesis of heterogeneous structures. At the same time, the material realizes the effective regulation of the built-in electric field at the interface, and also provides new ideas for other fields such as photocatalysis and energy batteries. More importantly, it provides technical reference for related sensors, such as photoelectrochemical sensors, electrochemical sensors, etc., and has broad potential use value.

[0052] The beneficial effects of this application include:

[0053] 1) The ethanol gas sensor provided in the present application is simple to prepare and easy to operate, and can achieve rapid, sensitive, and highly selective detection of ethanol gas molecules at a low cost. In addition, the test conditions close to room temperature provide conditions for portable detection of the sensor, and have market development prospects.

[0054] 2) The present application provides a method for preparing Co-based oxides anchored by defect-rich g-C3N4. The defects in this invention have the function of "killing two birds with one stone". First, the existence of defects is conducive to the adsorption of metal ions on its surface, providing attachment sites for the subsequent growth of MOFs structure. Secondly, the defects can enhance the accessibility of the material to the target gas molecules in the subsequent sensing process, which is conducive to the improvement of gas sensing performance.

[0055] 3) The design of the g-C3N4-based composite structure provided in this application provides a new idea. Using defects as sites to realize the construction of heterostructures can expand the types of g-C3N4 family materials. At the same time, the synergistic effect between defects and subsequent heterojunction structures also provides new material design strategies for fields other than gas sensing. In summary, the simple and effective preparation of this material has important scientific significance and application value. BRIEF DESCRIPTION OF THE DRAWINGS

[0056] Figure 1 This is the XRD pattern of the defect-rich g-C3N4-anchored Co-based oxide gas sensing material prepared in Example 1 of the present application.

[0057] Figure 2 This is a working curve diagram of the gas sensor in Example 1 of the present application.

[0058] Figure 3 This is a gas sensor selectivity diagram in Example 12 of the present application. DETAILED DESCRIPTION

[0059] The present application is described in detail below with reference to embodiments, but the present application is not limited to these embodiments.

[0060] Unless otherwise specified, the raw materials in the examples of this application were purchased through commercial channels.

[0061] In the examples of the present application, the following instruments are used to characterize the Co-based oxide gas sensing material based on the anchoring of defect-rich g-C3N4:

[0062]

[0063]

[0064] Example 1 Preparation of defect-rich g-C3N4 anchored Co-based oxide gas sensing material

[0065] (1) 0.5 g of melamine was placed in a crucible and heated from room temperature to 550°C in a muffle furnace at a heating rate of 5°C / min. The temperature was maintained at 550°C for 4 h. After the muffle furnace was cooled to room temperature, g-C3N4 was obtained.

[0066] (2) 0.5 g of the g-C3N4 obtained in (1) was dissolved in a 1 M NaOH solution, stirred at room temperature, and the product was collected, centrifuged three times, washed with ethanol solvent, and dried at 60°C for 5 h to obtain defect-rich g-C3N4.

[0067] (3) 0.5 g of cobalt nitrate and 0.5 g of defect-rich g-C3N4 in (2) were dissolved in 40 ml of methanol, labeled as solution A. Solution B was prepared by dissolving 0.5 g of 2-methylimidazole in 40 ml of methanol. Solution B was slowly poured into solution A under constant magnetic stirring at 1500 rpm at ambient temperature for 1 h. The product was collected by centrifugation 3 times, washed with ethanol solvent, and dried at 60 °C for 3 h to obtain a g-C3N4-Co MOFs composite structure.

[0068] (4) The g-C3N4-Co MOFs composite structure obtained in (3) was placed in a crucible and maintained at 500°C for 4 h at a heating rate of 5°C / min. After cooling to room temperature, g-C3N4-Co3O4 was obtained, wherein the loading amount of Co3O4 was about 10 wt%. Figure 1 It can be seen that the prepared material has a good crystal form.

[0069] Example 2

[0070] (1) 0.6 g of melamine was placed in a crucible and heated from room temperature to 500°C in a muffle furnace at a heating rate of 5°C / min. The temperature was maintained at 500°C for 4 h. After the muffle furnace was cooled to room temperature, g-C3N4 was obtained.

[0071] (2) 0.6 g of the g-C3N4 obtained in (1) was dissolved in a 2 M NaOH solution and stirred at room temperature. The product was collected, centrifuged three times, washed with ethanol solvent, and dried at 60°C for 5 h to obtain defect-rich g-C3N4.

[0072] (3) 0.7 g of cobalt nitrate and 0.7 g of defect-rich g-C3N4 in (2) were dissolved in 40 ml of methanol, labeled as solution A. Solution B was prepared by dissolving 0.5 g of 2-methylimidazole in 40 ml of methanol. Solution B was slowly poured into solution A under constant magnetic stirring at 1500 rpm at ambient temperature for 1 h. The product was collected by centrifugation 3 times, washed with ethanol solvent, and dried at 60 °C for 3 h to obtain a g-C3N4-Co MOFs composite structure.

[0073] (4) The g-C3N4-Co MOFs composite structure obtained in (3) was placed in a crucible and maintained at 500°C for 4 h with a heating rate of 5°C / min. After cooling to room temperature, g-C3N4-Co3O4 was obtained, in which the Co3O4 loading was about 12 wt%.

[0074] Example 3

[0075] (1) 0.6 g of melamine is placed in a crucible and heated from room temperature to 500°C in a muffle furnace at a heating rate of 5°C / min. The temperature is maintained at 500°C for 4 hours. The muffle furnace is cooled to room temperature to obtain g-C3N4, wherein g-C3N4 is repeatedly calcined in a muffle furnace for multiple times as needed.

[0076] (2) Dissolve 1 g of g-C3N4 obtained in (1) in 1 M NaOH solution, stir at room temperature, collect the product, centrifuge 3 times, wash with ethanol solvent, and dry at 60°C for 7 h to obtain defect-rich g-C3N4.

[0077] (3) 0.7 g of cobalt chloride and 0.7 g of defect-rich g-C3N4 in (2) were dissolved in 40 ml of methanol, labeled as solution A. Solution B was prepared by dissolving 0.5 g of 2-methylimidazole in 40 ml of methanol. Solution B was slowly poured into solution A under constant magnetic stirring at 1500 rpm at ambient temperature for 1 h. The product was collected by centrifugation 3 times, washed with ethanol solvent, and dried at 60 °C for 3 h to obtain a g-C3N4-Co MOFs composite structure.

[0078] (4) The g-C3N4-Co MOFs composite structure obtained in (3) was placed in a crucible and maintained at 500°C for 4 h with a heating rate of 5°C / min. After cooling to room temperature, g-C3N4-Co3O4 was obtained, in which the Co3O4 loading was about 12 wt%.

[0079] Example 4 Preparation of defect-rich g-C3N4 anchored Co-based oxide gas sensing material

[0080] (1) 0.6 g of melamine was placed in a crucible and heated from room temperature to 550°C in a muffle furnace at a heating rate of 5°C / min. The temperature was maintained at 550°C for 6 h. After the muffle furnace was cooled to room temperature, g-C3N4 was obtained.

[0081] (2) 0.7 g of the g-C3N4 obtained in (1) was dissolved in a 2 M NaOH solution and stirred at room temperature. The product was collected, centrifuged three times, washed with ethanol solvent, and dried at 60°C for 7 h to obtain defect-rich g-C3N4.

[0082] (3) 0.5 g of cobalt chloride and 0.5 g of defect-rich g-C3N4 in (2) were dissolved in 40 ml of methanol, labeled as solution A. Solution B was prepared by dissolving 0.5 g of 2-methylimidazole in 40 ml of methanol. Solution B was slowly poured into solution A under constant magnetic stirring at 1500 rpm at ambient temperature for 1 h. The product was collected by centrifugation 3 times, washed with ethanol solvent, and dried at 60 °C for 3 h to obtain a g-C3N4-Co MOFs composite structure.

[0083] (4) The g-C3N4-Co MOFs composite structure obtained in (3) was placed in a crucible and maintained at 550°C for 4 h with a heating rate of 5°C / min. After cooling to room temperature, g-C3N4-Co3O4 was obtained, in which the Co3O4 loading amount was about 10 wt%.

[0084] Example 5 Preparation of defect-rich g-C3N4 anchored Co-based oxide gas sensing material

[0085] (1) 0.65 g of melamine was placed in a crucible and heated from room temperature to 500°C in a muffle furnace at a heating rate of 5°C / min. The temperature was maintained at 500°C for 4 h. After the muffle furnace was cooled to room temperature, g-C3N4 was obtained.

[0086] (2) Dissolve 1 g of the g-C3N4 obtained in (1) in a 2 M NaOH solution, stir at room temperature, collect the product, centrifuge it three times, wash it with ethanol solvent, and dry it at 60°C for 7 h to obtain defect-rich g-C3N4.

[0087] (3) 1.0 g of cobalt chloride and 1.0 g of defect-rich g-C3N4 in (2) were dissolved in 40 ml of methanol, labeled as solution A. Solution B was prepared by dissolving 0.5 g of 2-methylimidazole in 40 ml of methanol. Solution B was slowly poured into solution A under constant magnetic stirring at 1500 rpm at ambient temperature for 2 h. The product was collected by centrifugation 3 times, washed with ethanol solvent, and dried at 80 °C for 3 h to obtain a g-C3N4-Co MOFs composite structure.

[0088] (4) The g-C3N4-Co MOFs composite structure obtained in (3) was placed in a crucible and maintained at 500°C for 4 h with a heating rate of 5°C / min. After cooling to room temperature, g-C3N4-Co3O4 was obtained, in which the Co3O4 loading was about 20 wt%.

[0089] Example 6

[0090] (1) 0.4 g of melamine was placed in a crucible and heated from room temperature to 550°C in a muffle furnace at a heating rate of 5°C / min. The temperature was maintained at 550°C for 4 h. After the muffle furnace was cooled to room temperature, g-C3N4 was obtained.

[0091] (2) 0.4 g of the g-C3N4 obtained in (1) was dissolved in a 2 M NaOH solution and stirred at room temperature. The product was collected, centrifuged three times, washed with ethanol solvent, and dried at 60°C for 7 h to obtain defect-rich g-C3N4.

[0092] (3) 0.7 g of cobalt chloride and 0.7 g of defect-rich g-C3N4 in (2) were dissolved in 40 ml of methanol, labeled as solution A. Solution B was prepared by dissolving 0.5 g of 2-methylimidazole in 40 ml of methanol. Solution B was slowly poured into solution A under constant magnetic stirring at 1500 rpm at ambient temperature for 1 h. The product was collected by centrifugation 3 times, washed with ethanol solvent, and dried at 60 °C for 3 h to obtain a g-C3N4-Co MOFs composite structure.

[0093] (4) The g-C3N4-Co MOFs composite structure obtained in (3) was placed in a crucible and maintained at 500°C for 4 h with a heating rate of 5°C / min. After cooling to room temperature, g-C3N4-Co3O4 was obtained, in which the Co3O4 loading was about 15 wt%.

[0094] Example 7

[0095] (1) 0.7 g of melamine was placed in a crucible and heated from room temperature to 500°C in a muffle furnace at a heating rate of 5°C / min. The temperature was maintained at 500°C for 6 h. After the muffle furnace was cooled to room temperature, g-C3N4 was obtained.

[0096] (2) Dissolve 1 g of g-C3N4 obtained in (1) in 1 M NaOH solution, stir at room temperature, collect the product, centrifuge 3 times, wash with ethanol solvent, and dry at 60°C for 7 h to obtain defect-rich g-C3N4.

[0097] (3) 0.7 g of cobalt acetate and 0.7 g of defect-rich g-C3N4 in (2) were dissolved in 40 ml of methanol, labeled as solution A. Solution B was prepared by dissolving 0.5 g of 2-methylimidazole in 40 ml of methanol. Solution B was slowly poured into solution A under constant magnetic stirring at 1500 rpm at ambient temperature for 1 h. The product was collected by centrifugation 3 times, washed with ethanol solvent, and dried at 60 °C for 3 h to obtain a g-C3N4-Co MOFs composite structure.

[0098] (4) The g-C3N4-Co MOFs composite structure obtained in (3) was placed in a crucible and maintained at 500°C for 4 h with a heating rate of 5°C / min. After cooling to room temperature, g-C3N4-Co3O4 was obtained, in which the Co3O4 loading was about 15 wt%.

[0099] Example 8

[0100] (1) 0.6 g of dicyandiamide was placed in a crucible and heated from room temperature to 500°C in a muffle furnace at a heating rate of 5°C / min. The temperature was maintained at 500°C for 4 h. After the muffle furnace was cooled to room temperature, g-C3N4 was obtained.

[0101] (2) Dissolve 1 g of the g-C3N4 obtained in (1) in a 2 M NaOH solution, stir at room temperature, collect the product, centrifuge it three times, wash it with ethanol solvent, and dry it at 60°C for 7 h to obtain defect-rich g-C3N4.

[0102] (3) 0.5 g of cobalt acetate and 0.5 g of defect-rich g-C3N4 prepared in (2) were dissolved in 40 ml of methanol, which was labeled as solution A. Solution B was prepared by dissolving 0.5 g of 2-methylimidazole in 40 ml of methanol. Solution B was slowly poured into solution A under constant magnetic stirring at 1500 rpm at ambient temperature for 1 h. The product was collected by centrifugation 3 times, washed with ethanol solvent, and dried at 60 °C for 3 h to obtain a g-C3N4-Co MOFs composite structure.

[0103] (4) The g-C3N4-Co MOFs composite structure obtained in (3) was placed in a crucible and maintained at 500°C for 4 h with a heating rate of 5°C / min. After cooling to room temperature, g-C3N4-Co3O4 was obtained, in which the Co3O4 loading amount was about 10 wt%.

[0104] Comparative Example 1

[0105] The prepared g-C3N4 was directly subjected to step (3) to react with Co precursor and 2-methylimidazole, and centrifuged and washed to obtain a g-C3N4-Co MOFs composite structure. The obtained product was then placed in a crucible, maintained at 500°C for 4 hours, with a heating rate of 5°C / min, and cooled to room temperature to obtain g-C3N4-Co3O4, wherein the loading amount of Co3O4 was 10wt%.

[0106] Example 9 Construction of ethanol gas sensor

[0107] (1) Using the interdigital electrode as the gas sensing electrode, the defect-rich g-C3N4 anchored Co-based oxide gas sensing material prepared in Example 1 was added to 5 mL of water and mixed to form a uniform slurry. Then 10 μL of the slurry was dropped on the surface of the substrate with Ag-Pd printed interdigital electrodes. The electrode was dried at 80°C to form a sensing film.

[0108] (2) The electrode obtained in step (1) is then heated in an oven to 200° C. for 5 hours to remove the residual organic solvent, thereby obtaining an ethanol gas sensor.

[0109] Example 10 Construction of ethanol gas sensor

[0110] (1) Using the interdigital electrode as the gas sensing electrode, the defect-rich g-C3N4 anchored Co-based oxide gas sensing material prepared in Example 3 was added to 5 mL of anhydrous ethanol and mixed to form a uniform slurry. Then 5 μL of the slurry was dropped on the surface of the substrate with Ag-Pd printed interdigital electrodes. The electrode was dried at 60°C to form a sensing film.

[0111] (2) The electrode obtained in step (1) is then heated to 180° C. in an oven for 3 hours to remove the residual organic solvent, thereby obtaining an ethanol gas sensor.

[0112] Comparative Example 2

[0113] Supplementary use of the defect-free material of Comparative Example 1 to construct an ethanol gas sensor

[0114] (1) Using the interdigital electrode as the gas sensing electrode, the gas sensing material prepared in Ratio 1 was added to 5 mL of anhydrous ethanol and mixed to form a uniform slurry. Then 5 μL of the slurry was dropped on the surface of the substrate with Ag-Pd printed interdigital electrodes. The electrode was dried at 60°C to form a sensing film.

[0115] (2) The electrode obtained in step (1) is then heated to 180° C. in an oven for 3 hours to remove the residual organic solvent, thereby obtaining an ethanol gas sensor.

[0116] Embodiment 11

[0117] The ethanol gas sensors prepared in Examples 9 and 10 and Comparative Example 2 are applied to the detection of ethanol gas molecules, and the steps are as follows:

[0118] (1) Preparation of gas sensing electrode: The ethanol gas sensor constructed in Example 10 was used as the working electrode;

[0119] (2) Standard gas configuration: To obtain the required gas, ethanol liquid was added into the test chamber using a micro syringe and evaporated directly;

[0120] (3) Working curve drawing: The electrodes described in (1) are connected to the gas sensor detection equipment, and the gas is distributed in the gas chamber using the method described in (2); the resistance of the sensor before and after ventilation is tested in the chamber with relative humidity (RH = 20%) and constant temperature (determined by the sensor working temperature); a working curve is drawn based on the relationship between the resistance change and the ethanol concentration; the resistance change is measured by R g / R a Indicates that R a refers to the resistance in ambient air, while R g is the resistance in the measured gas; the working curve takes the concentration of ethanol gas molecules as the horizontal axis, R g / R a is plotted as the vertical axis. Figure 2 It can be seen that the sensor shows a good linear range for ethanol.

[0121] Example 12

[0122] Inject interfering gas molecules with the same concentration as ethanol into the chamber, test their gas-sensitive properties, and obtain the selectivity of the sensor. (The test method and test conditions are consistent with those of ethanol gas detection); Figure 3 It can be seen that the sensor has good selectivity for ethanol molecules.

[0123] The above are only a few embodiments of the present application and do not constitute any form of limitation to the present application. Although the present application is disclosed as above with preferred embodiments, it is not intended to limit the present application. Any technician familiar with the profession, without departing from the scope of the technical solution of the present application, using the technical content disclosed above to make slight changes or modifications are equivalent to equivalent implementation cases and fall within the scope of the technical solution.

Claims

1. A method for preparing a Co-based oxide material based on g-C3N4 anchoring, characterized in that: The preparation method comprises the following steps: (1) calcining the N-containing precursor to obtain g-C3N4; (2) etching the g-C3N4 with an alkaline solution, centrifuging I, and drying I to obtain defect-rich g-C3N4; (3) A mixture of defect-rich g-C3N4, Co precursor, 2-methylimidazole, and solvent is reacted, centrifuged II, dried II, and calcined II to obtain the Co-based oxide material anchored by g-C3N4.

2. The preparation method according to claim 1, characterized in that: In the step (1), the N-containing precursor is selected from at least one of melamine, urea and dicyandiamide.

3. The preparation method according to claim 1, characterized in that: The mass volume ratio of the g-C3N4 to the alkaline solution is 0.5-1 g: 10-20 mL; Preferably, in step (2), the alkaline solution is selected from NaOH and / or KOH; Preferably, the concentration of the alkaline solution is 0.1M to 0.5M.

4. The preparation method according to claim 1, characterized in that: The mass ratio of the Co precursor, defect-rich g-C3N4, and 2-methylimidazole is 0.5g-1g: 0.01g-0.05g: 0.01g-0.05g; Preferably, the Co precursor is selected from at least one of cobalt chloride, cobalt nitrate, cobalt acetate, and organic cobalt; Preferably, the organic cobalt is selected from at least one of cobalt acetylacetonate and cobalt naphthenate; Preferably, the solvent is selected from at least one of methanol, water and ethanol.

5. The preparation method according to claim 1, characterized in that: The etching time is 12 to 24 hours; Preferably, in step (3), the reaction temperature is 20 to 80° C., and the reaction time is 1 to 24 hours.

6. The preparation method according to claim 1, characterized in that: The number of centrifugation I and centrifugation II is independently selected from 3 to 7 times; Preferably, the temperatures of drying I and drying II are independently selected from 50 to 85° C., and the times of drying I and drying II are independently selected from 12 to 16 hours.

7. The preparation method according to claim 1, characterized in that: The temperatures of the calcination I and calcination II are independently selected from 500 to 700° C., and the times of the calcination I and calcination II are independently selected from 4 to 6 hours.

8. The Co-based oxide material based on g-C3N4 anchoring prepared by the preparation method according to any one of claims 1 to 7, characterized in that: The Co-based oxide in the Co-based oxide material anchored by g-C3N4 is Co3O4; The loading amount of Co3O4 in the g-C3N4 anchored Co-based oxide material is 5wt% to 20wt%.

9. The use of the Co-based oxide material anchored by g-C3N4 in an ethanol gas sensor according to claim 8, characterized in that: The detection limit of the ethanol gas sensor for ethanol is 300-350 ppb.

10. The use according to claim 9, characterized in that: The operating temperature of the ethanol gas sensor is 100-150°C.

Citation Information

Patent Citations

  • Carbon-based adsorbent for mercury removal as well as preparation method and application thereof

    CN111250042A

  • Method for treating waste gas by using cobaltosic oxide dodecahedron / carbon nitride nanosheet compound

    CN112958137A

  • Co atom-doped polyhedral MOFs (Metal-Organic Frameworks) material as well as preparation method and application thereof

    CN113410481A

  • Preparation method and application of Co-based two-dimensional metal oxide gas sensing material

    CN119706960A

  • Method of methane oxidation

    GB202106079D0

Cited By

  • Mellitene-based molecularly confined ternary gas sensing material and preparation method thereof

    CN122671495A